(untitled) (Research, Society and Development, 2022)
The consumption of water by human beings is indispensable, however, it must be free of contamination, whether chemical, physical, biological or microbiological, and for that reason it must be treated according to rules established by inspection or public health agencies, contributing to eliminate possible microorganisms existing in it before consumption. The general objective is to analyze the importance of the microbiological quality of water for human consumption and the impact on human health that untreated water can cause. A systematic review of scientific articles was carried out, using the PRISMA method of studies published between the years 2012 to 2022 written in Portuguese, English and Spanish in Scielo and PubMed digital databases, which were selected and analyzed the data related to the theme quoted to compose the body and development of this review article in the form of descriptive explanatory summaries for a better understanding of the collected data. Information was collected from 19 articles, 10 main and 9 reinforcing, among the collected information, tests were obtained in reservoirs, in schools, independent sources and the situation in which Brazil finds itself regarding the coverage and microbiological quality of water. Brazil has evolved slowly in coverage and water quality control. Where it is concluded that specialized professionals such as Pharmacists, can contribute to the collection and analysis of samples, contributing with their findings to alert decision makers about the possibilities of disease occurrences due to contamination of the water served to the population.